Tecnologias de fertilizantes nitrogenados na cafeicultura - Chagas, Wantuir Filipe Teixeira (2017)
The application of stabilized, slow release and controlled-release nitrogen fertilizers and their blends may reduce losses of N-NH3 in comparison to conventional urea. This reduction in the losses of N may enhance the use and recovery of N by plants. In the first part of the study, the aim was to assess the growth, nutritional, and physiological characteristics and the agronomic efficiency of the nitrogen fertilization with stabilized, slow and controlled-release fertilizers and ‘blends’ in the growth of coffee seedlings (Chapter 1). The experiment was performed in greenhouse in pots with volume of 14 L. The following nitrogen fertilizers were applied in the dose of 10 g pot -1 of N, which were split in three applications with interval of 50 days between each application: conventional urea; ammonium nitrate, urea + formaldehyde; Polyblen Extend ® ; PolyblenMontanha®; urea + polyurethane; urea + plastic resin; ammonium sulfate + CaCO 3 and the control, without N application. The highest values of plant height, total dry mass of plants and leaf area in coffee seedlings were found with the application of Polyblen Extend ® . This blend provided higher N accumulation in the leaf and in the whole plant. The application of Polyblen Extend ® also provided higher agronomic efficiency and enhanced the photosynthetic rate and the chlorophyll relative index in the coffee seedlings at the end of the experimental period. In the second part of the experiment, the aim was to quantify the losses of N by ammonia volatilization and their changes in the nutritional parameters, in the yield and agronomic efficiency, after the application of conventional nitrogen fertilizers and ‘blends’ in top dressing of coffee crop in production (Chapter 2). The experiment was performed in the field, in the growing season of 2014/2015 and 2015/2016, in a Clayey Red Oxisol. It was used the randomized block design with six treatments: T1 = granulated urea applied at a dose of 450 kg of N ha -1 year -1 (100% of recommended dose) in three equals splitting with intervals of 50 days; T2 = ammonium nitrate applied in the dose of 450 kg of N ha -1 year -1 (100% of the recommended dose) in three equal splitting with interval of 50 days; T3 = Polyblen Extend ® (100% of the recommended dose) applied in two splitting (70% of the total N dose in the 1 st and 30% in the 2 nd splitting); T4 = Polyblen Extend ® (70% of total N dose in the 1 st and 30% in the 2 nd splitting); T5 = PolyblenMontanha (100% of the recommended dose) without splitting; T6 = PolyblenMontanha® (70% of the recommended dose) without splitting, with three repetitions. In the average of two years of evaluation, urea provided the highest losses by N-NH3 volatilization when compared with the other nitrogen fertilizers applied in the coffee crop. Ammonium nitrate provided lower losses of N by volatilization. Polyblen Extend ® and PolyblenMontanha® reduced losses by volatilization in comparison to urea. The application of ammonium nitrate and blends (Polyblen Extend ® andPolyblenMontanha®) enhanced the coffee crop yield in comparison to the application of urea. With the application of urea, there was a need of more liters of natural coffee (café da roça) to make a bag of 60 kg of benefited coffee. Pol yblen Extend ® and PolyblenMontanha® provided the same yield by applying 100 and 70% of the recommended dose. Ammonium nitrate and PolyblenMontanha – 100% presented higher relative agronomic efficiency index. Urea provided lower agronomic efficiency among the nitrogen fertilizers. In the average of the two years (2015-2016), ammonium nitrate, Polyblen Montanha® 100% and Polyblen Montanha® 70% promoted a higher percentage of flat borer grains. At the end of the two years, ammonium nitrate, Polyblen Extend® 100%, Polyblen Montanha® 70% and Polyblen Montanha® 100% promoted greater accumulation of caffeine in coffee beans. And ammonium nitrate and Polyblen Montanha® 100% promoted the greatest accumulation of total sugars.